ACTIVATED PARTIAL THROMBOPLASTIN TIME AND FIBRINOGEN IN PEDIATRIC NEPHROTIC SYNDROME DURING RELAPSE AND REMISSION - Tarigan, Trianita; Aman, Adi Koesoema; Ramayani, Oke Rina (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Nephrotic Syndrome (NS) is a complicated kidney disease disorder, one of the most important complications is thromboembolism which can affect the circulation, either arterial or venous in both pediatric and adult patients. Patients at risk of thromboembolism should have an angiography examination for diagnosis. There have been several studies conducted on patients with a nephrotic syndrome showing the risk of thromboembolism. This study included twelve patient of pediatric nephrotic syndrome consisting of males and females. The patient experiences a period of relapse and became a remission. Patients participating in the study were 3 to 17 years old. There were significant differences in fibrinogen in which the fibrinogen content of NS patients in children at relapse was higher compared with the time of remission (390.08 ± 164.87 vs. 273.17 ± 150.56; p=0.042). There was no significant difference in Activated Partial Thromboplastin Time (APTT) results in SN patients in relapse compared to remission (34.17 ± 5.65 vs. 30.08 ± 8.49; p=0.236). The high levels of fibrinogen in the relapse period indicate the presence of hypercoagulable state, along with other examinations such as high cholesterol and low albumin. In this study, there was no significant difference in APTT among SN patients during relapse compared with remission while in the fibrinogen examination a significant difference was found. Therefore, fibrinogen examination is important to be analyzed in order to avoid SN complications.